ASSISTANCE IN FINANCIAL TRANSACTION RECORDING TRAINING AT THE KAKI LANGIT TOURISM VILLAGE - Edi Iskandar; Sur Yanti; Herdiesel Santoso; Istika Dwi Kusumaningrum (Bajang Institute, 2022)
Financial information such as information on capital turnover, profits generated or assets owned by the company is important, so that the recording must be done properly. Kaki Langit Tourism Village has problems in recording financial transactions because the management does not understand the correct recording of financial transactions in producing financial information. The method used in the Financial Transaction Recording Training Assistance activity at the Kaki Langit Tourism Village is the Participatory Action Research (PAR) method. The assistance carried out by the service team uses the PAR method whose implementation includes several stages, namely the introduction to Accounting and the recording process, the recording stage, the posting stage, the balance sheet preparation stage, the adjustment process stage and the 10-column Worksheet, and the Financial Statement stage. At the end of the mentoring, the manager of the Kaki Langit Tourism Village has knowledge that is applied in recording business financial transactions so as to produce financial information that can be used in decision making.